تشجيع المنتوج الوطني في اطار السياسة الصناعية الجديدة في الجزائر - طيبي, حمزة; تومي, ابراهيم (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدراسة إلى تسليط الضوء على المجهودات التي بذلتها السلطات العمومية الجزائر ية من أجل تحقيق التنويع الاقتصادي والتخلص من التبعية لقطاع المحروقات، وذلك من خلال تشجيع المنتوج الوطني والنهوض بالقطاع الصناعي وتطويره باعتباره قطاعا مكملا لبقية القطاعات الاقتصادية الأخرى، الأمر الذي يتطلّب اعتماد سياسة اقتصادية يتم استخدام اجراءاتها المختلفة سواء الظرفية أو الهيكلية أو كليهما في تنمية القطاعات الاقتصادية عامة و القطاع الصناعي على وجه الخصوص نتيجة التفاعل بين توظيف الأموال مع عملية الانتاج وما يترتّب عليها من زيادة التشغيل وزيادة الوعاء الضريبي..الخ، وفي هذا الاطار فقد ركّزت هذه الدراسة على موضوع تشجيع المنتوج الوطني في إطار السياسة الصناعية الجديدة في الجزائر. وقد توصلت الدراسة إلى أن الحكومة الجزائرية قامت بجهود كبيرة في سبيل تطوير المنتوج الوطني الصناعي، إلا أنّ النتائج المحقّقة لم ترقى الى المستوى المطلوب. This study aims to shed light on the efforts made by the Algerian public authorities in order to achieve economic diversification and get rid of dependency on the hydrocarbons sector, through the encouragement of the national product and the advancement and development of the industrial sector as a sector complementary to the rest of the other economic sectors, which requires the adoption of an economic policy that is done The use of its various measures, whether circumstantial or structural, or both, in the development of the economic sectors in general and the industrial sector in particular, as a result of the interaction between the employment of funds with the production process and the consequent increase in employment and the increase of the tax base..Etc, In this context, this study focused on the issue of encouraging the national product within the framework of the new industrial policy in Algeria. The study concluded that the Algerian government has made great efforts to develop the national industrial product, but the results achieved did not live up to the required level.
Keywords: تشجيع المنتوج الوطني في اطار السياسة الصناعية الجديدة في الجزائر